(untitled) (BIRDEM Medical Journal, 2021)
Precocious puberty is commonly defined as puberty that starts before age 8 years in girls and 9 years in boys. The causes of it may range from a variant of normal development to various pathologic conditions. The etiology of precocious puberty is classified by the underlying pathogenesis into gonadotropin dependent central precocious puberty and peripheral precocious puberty which is independent of gonadotropin but due to different other causes. Variants of precocious puberty include premature thelarche, premature puberche and isolated premature menarche which imply onset of isolated changes without any other signs of sexual development. Precocious puberty might have an impact on final stature owing to premature epiphyseal fusion and also it has got influence on psychosocial wellbeing. Evaluation includes a detailed history, physical examination, biochemical testing and imaging directed towards suspected etiology. Gonadotropin releasing hormone (GnRH) analogues are effective for treatment of central precocious puberty. Treatment of peripheral precocious puberty should be based on the specific cause. Pubertal variants are usually non-progressive and need no treatment but should be monitored carefully. BIRDEM Med J 2022; 12(1): 62-69